THE EFFECT OF EDUCATIONAL METHODS BASED ON THE VISUAL REPRESENTATIONAL SYSTEM IN LEARNING THE SKILL OF JAVELIN THROWING FOR FIRST-YEAR STUDENTS IN THE COLLEGE OF BASIC EDUCATION - Assistant teacher RUSUL AYAD GHAIDAN (Proximus Journal Publishing, 2025)
The research aims to prepare educational units according to the visual system in learning the skill of javelin throwing for first-year students in the College of Basic Education, and to identify the effect of the educational methods used according to the visual system in learning the skill of javelin throwing for members of the research sample. To achieve the goal, the researcher used the experimental method and designed two equal experimental and control groups with a pre- and post-test to suit the problem and objectives of the research. The research population was limited to the students of the first stage of morning study in the Department of Physical Education and Sports Sciences - College of Basic Education - Al-Mustansiriya University, for the academic year 2023-2024, and their number is ( 115) students They were distributed into (6) divisions, namely (A - B - C - D - E - F). The research population was determined by the students of the first stage, as this stage teaches the skill of spear throwing. As for the research sample, they were chosen by lottery among the divisions to determine the groups (experimental and control). Then the researcher identified (25) students from each section by lottery as follows: Section B (25) students, Section E (25) students, and their total number reached (50) students, with a percentage of (43.47%), as they were divided into two groups. control and experimental, The experimental group, which is Division (B), will learn the skill of javelin throwing according to the teaching methods according to the visual representational system, and the control group, which is Division (E), will learn in the method used by the teacher (the imperative method) and according to the curriculum of the prescribed physical education lesson, The researcher conducted the pre- and post-test for the experimental and control groups, and conducted the appropriate statistical treatments. The researcher concluded that the use of educational methods in the educational curriculum was effective in improving the skill aspect of the experimental group, and that there was a relative improvement in the visual representational system among the learners and towards integration
Keywords: Visual representational system; javelin throw